ANALISIS BASIS EKONOMI SUBSEKTOR INDUSTRI PENGOLAHAN HASIL PERTANIAN DAN KEHUTANAN DI KOTA BANDAR LAMPUNG - Manik, Yunika Hutami; Ismono, R. Hanung; Yanfika, Helvi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
The purpose of this study was to analyze the role of industry sub-sectors of agriculture and forestry product processing in Bandar Lampung on the theory of the economic base. The data used were secondary data from various institutions which was analyzed by analytical tools of location quotient (LQ), and the multiplier effect. The research results showed that the manufacture as sub-sectors of agriculture and forestry in Bandar Lampung has a value of LQ > 1 in which average was 1.3654 (Base). The role of the industry sub-sectors of agriculture and forestry product processing in Bandar Lampung was in the economic base region. Any change in the average income of Rp1, the subsector of agriculture and forestry product processing could increase the total revenue of Rp5.90. The average change in total revenues in Bandar Lampung in the year of 2006-2010 amounted to Rp374,619,000,000. It is suggested that the manufacturing subsector is more developed together with the community and all policy holders in Bandar Lampung industry sub sectors, namely food, beverages, and tobacco, due to its rapid growth and competitiveness. In addition, to improve the economic could also be one of the tourist attractions in Bandar Lampung as the city’s of “Tapis Berseri”. Keywords: economic base, industrial processing of agricultural and forestry, location quotion